PENGARUH PENGEMASAN VAKUM TERHADAP KERUSAKAN BIJI JAGUNG (Zea mays L.) - Novia Basriadi; Lady Corrie E. Ch. Lengkey; Frans Wenur (Universitas Sam Ratulangi, 2018)
ABSTRACT The main problem during corn storage is the attack of insects and fungi. Packaging is one way to overcome this problem. The purpose of this study was to determine the initial and final moisture content of vacuum-packed corn kernels, without vacuum packaging and without packaging, as well as to calculate damage to dried corn during storage. The research method was the experimental method of Completely Randomized Design (RAL) using three treatments: vacuum packaging, without vacuum packaging and without packaging. Then the material is stored for two months at room temperature. The results showed that the lowest damage percentage of corn seeds stored at an average room temperature of 27.7oC was obtained in a vacuum packaging treatment with insect damage rate of 6.31%, fungal damage of 8.96%, with an average moisture content average of 14.19%. Keywords : Dried Corn, Vacuum Packaging, Insect and Fungi Damage